A Novel Approach to Power Quality Analysis: Adaptive FEM Algorithm with Sparse Signal Decomposition. Issue 9 (16th July 2020) - Rahul,
Abstract: An adaptive approach of discretized triangular mesh based on finite element method hybrid with type‐2 fuzzy is utilized for detection and classification of power quality events. The concept of sparse signal decomposition is utilized with extraction of disturbances from power signals. An adaptive finite element method is then applied with the concept of stiffness matrix which extracts some relevant features of power quality events that act as input to type‐2 fuzzy classifiers. Finally performance comparison is carried out, the results of which show that the proposed technique has potential to analyze disturbances with high accuracy and minimum computational overhead. Abstract : Power quality disturbances are a major concern due to increasing nonlinear loads into systems. To deal with this issue an adaptive finite element method approach with type‐2 fuzzy based classifier is an effective way as it requires less computation time and exhibits high accuracy. This approach has the capability to analyze power quality disturbances in real time.